The influence of different sources of polyphenols on sub- maximal cycling and time trial performance - Clifford, T.; Mitchell, N.; Scott, A. (Journal of Athletic Enhancement, 2013)
The primary purpose of the study was to establish the effects of commercially available polyphenol-rich antioxidant supplements, Pycnogenol® with added bioflavonoids (PYC-B) and CherryActive (CHA), on 20 km cycling performance. Using a double-blind counterbalanced, repeated-measures design, nine male cyclists or triathletes (32.1 ± 11.2 years; maximal aerobic capacity 4.2 ± 0.7 L•min-1; maximal power output 391.7 ± 39.5 watts) consumed 200 mg of CHA, 120 mg of PYC-B, or 200 mg of placebo (PLA) capsules, 2 days before and on the day of each experimental trial. The experimental trials consisted of four 5 minute stages at 40%, 50%, 60%, and 70% maximal power output (Wmax), followed by a 20 km time trial (TT). Statistical analysis revealed no significant differences between trials for heart rate, respiratory exchange ratio, gross mechanical efficiency, oxygen consumption, or blood lactate, at any of the intensities completed during the initial 20 minute phase of the trial (p>0.05). Final 20 km TT times were not significantly different between trials (p=0.115), but, compared to PLA, PYC-B did significantly increase power output by 6.2% over the final 5 km of the TT (p=0.022). The study suggests that the PYC-B supplement could be beneficial towards the end of an intense bout of cycling exercise. However, as total 20 km time was not significantly different between trials the doses used are unlikely to benefit 20 km cycling time trial performance.